2018
DOI: 10.3133/sir20185061
|View full text |Cite
|
Sign up to set email alerts
|

Comparability among four invertebrate sampling methods and two multimetric indexes, Fountain Creek Basin, Colorado, 2010–2012

Abstract: Vertical coordinate information is referenced to the North American Vertical Datum of 1988 (NAVD 88).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For instance, some of the macroinvertebrate communities in wadeable streams were sampled with the following codes: BERW, IRTH, SWAMP, EMAP, CDPHE, and PNAMP. All methods use kick net samplers with similar mesh sizes, and studies suggest that methods are similar in their ability to detect the presence and absence of taxa [28][29][30] . Fish are collected through seining, snorkelling, backpack or raft electrofishing, or some combination.…”
Section: Comparability Of Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some of the macroinvertebrate communities in wadeable streams were sampled with the following codes: BERW, IRTH, SWAMP, EMAP, CDPHE, and PNAMP. All methods use kick net samplers with similar mesh sizes, and studies suggest that methods are similar in their ability to detect the presence and absence of taxa [28][29][30] . Fish are collected through seining, snorkelling, backpack or raft electrofishing, or some combination.…”
Section: Comparability Of Sampling Methodsmentioning
confidence: 99%
“…Lumped Genera Group Lowest Common Taxonomic Designation Acentrella 1108 1269 1,2,4,5,6,8,11,12,13,14,15,16,17,18,19,21,22,23,25,26,27,28,29,31,32,33,34,35,40,41,42,44,45,46,49,51,52,53,58,59,61,66,67,68,69,70,71,72,74,75,76,77,78,80 Ephemeroptera Acerpenna 651 283 1,2,4,…”
Section: Number Of Usgs Samplesmentioning
confidence: 99%
“…In addition, to account for differences in sampling techniques and equipment, the following method codes for sampling events were selected: BERW, IRTH, SWAMP, EMAP, CDPHE, and PNAMP. Previous studies have suggested that these methods, which use similar mesh sizes, are comparable in their ability to detect the presence and absence of taxa (41)(42)(43). Only area-limited sample data were used.…”
Section: Data Managementmentioning
confidence: 99%